Neural probes with multi-drug delivery capability1. Issue 18 (21st September 2015) - Shin, Hyogeun; Lee, Hyunjoo J.; Chae, Uikyu; Kim, Huiyoung; Kim, Jeongyeon; Choi, Nakwon; Woo, Jiwan; Cho, Yakdol; Lee, C. Justin; Yoon, Eui-Sung; Cho, Il-Joo
<x xml:space="preserve">Abstract</x> Multi-functional neural probes are promising platforms to conduct efficient and effective in-depth studies of brain by recording neural signals as well as modulating the signals with various stimuli.